Copper and Temperature Interactions Induce Differential Physiological and Metal Exclusion Responses in the Model Brown Macroalga Ectocarpus - Alex Santillán-Sarmiento; Paula S. M. Celis-Plá; A. John Moody; Claudio A. Saez; Murray T. Brown (Plants)
The toxic effects of copper (Cu) excess in brown macroalgae have been well characterized. However, the interactive effects of increased temperatures, associated with climate change, and Cu stress on these macrophytes remain almost unexplored. In this study, we exposed the model brown seaweed Ectocarpus to different Cu concentrations (0, 0.8, 1.6, and 3.2 μM) at two different temperatures (15 and 25 °C). Relative growth rates decreased at 25 °C for the two highest Cu concentrations after 8 days of exposure, but a contrasting pattern was observed in the photosynthetic maximum quantum yield (Fv/Fm) and photosynthetic efficiency (α), where reductions were observed at 15 °C for the same Cu concentrations. Although no differences among treatments were observed for chlorophyll a (Chla) and chlorophyll c (Chlc), a reduction in concentration of the accessory pigment fucoxanthin (Fx) was only observed at 15 °C in all Cu treatments. Interestingly, at 25 °C, 20.1% less total Cu (intracellular + extracellularly bound) accumulated compared to 15 °C upon exposure to 3.2 μM Cu. Likewise, 33.1 and 23.8% less Cu accumulated intracellularly at 25 °C after exposure to 1.6 μM and 3.2 μM Cu, respectively. Additionally, at 25 °C about half of the Cu ions accumulated intracellularly and half extracellularly compared to 15 °C, where Cu accumulated mostly intracellularly at the two highest Cu concentrations. The results presented here provide valuable information to better understand the interactive effects of increased temperature and excess Cu in the stress response of Ectocarpus, suggesting that increased temperature helps to offset the negative impacts of exposure to high Cu concentrations.